In Focus/Dealing with Change Knowing Change Preferences Is a Boon for Leaders - Musselwhite, Christopher; Musselwhite, Christopher (Center for Creative Leadership, 2008)
How people deal with change--both creating it and responding to it--is a function of identifiable individual preferences. Whether people see change as a danger, a challenge, or an opportunity, they have individual preferences that reflect their relationship to structure, rules, and authority.